2014
DOI: 10.3758/s13415-014-0328-1
|View full text |Cite
|
Sign up to set email alerts
|

Different neural pathways linking personality traits and eudaimonic well-being: a resting-state functional magnetic resonance imaging study

Abstract: Eudaimonic well-being (EWB) is the fulfillment of human potential and a meaningful life. Previous studies have shown that personality traits, especially extraversion, neuroticism, and conscientiousness, significantly contribute to EWB. However, the neurobiological pathways linking personality and EWB are not understood. Here, we used restingstate functional magnetic resonance imaging (rs-fMRI) to investigate this issue. Specifically, we correlated individuals' EWB scores with the regional fractional amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 85 publications
2
29
0
Order By: Relevance
“…For example, the study of Kong et al . (2015b), which aimed to explore the neurobiological pathway linking personality and eudaimonic well-being in a big sample (N = 286), found that neuroticism is correlated with the fALFF in the posterior superior temporal gyrus (pSTG) (r = −0.15, P  = 0.048; FDR corrected) and thalamus (r = −0.20, P  = 0.005; FDR corrected) and the thalamic-insular connectivity (r = 0.17, P  = 0.021; FDR corrected). These correlation coefficients also ranged from 0.1 to 0.2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the study of Kong et al . (2015b), which aimed to explore the neurobiological pathway linking personality and eudaimonic well-being in a big sample (N = 286), found that neuroticism is correlated with the fALFF in the posterior superior temporal gyrus (pSTG) (r = −0.15, P  = 0.048; FDR corrected) and thalamus (r = −0.20, P  = 0.005; FDR corrected) and the thalamic-insular connectivity (r = 0.17, P  = 0.021; FDR corrected). These correlation coefficients also ranged from 0.1 to 0.2.…”
Section: Discussionmentioning
confidence: 99%
“…Future research using pharmacologic antagonists and experimental models will be required to determine whether such effects are mediated by such sympathetic/parasympathetic dynamics or perhaps by other neural or endocrine signaling pathways that may be engaged by eudaimonic well-being (Ryff, 2014; Ryff et al, 2006; Ryff et al, 2004; Taylor, 2006). Additional insights could also come from mapping the functional interactions between the CNS substrates of eudaimonia (Heller et al, 2013; Kong et al, 2015; Lewis et al, 2014; Telzer et al, 2014) and those involved in autonomic nervous system regulation (Beissner et al, 2013). Ancillary analyses identified CTRA associations with several other dimensions of affect and social perception, including positive and negative affect, anxiety symptoms, optimism (marginally), and pessimism.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred and ninety‐nine college students [159 females; mean age = 21.57 years, standard deviation (SD) = 1.01] from Beijing Normal University were recruited as paid participants. This study is as part of an ongoing research project to explore the associations among gene, environment, brain, and behavior [e.g., Kong et al, ; Wang et al, , in press]. Data that are irrelevant to the scope of this study were not reported here.…”
Section: Methodsmentioning
confidence: 99%